ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS BERDASARKAN MOTIVASI BELAJAR MATEMATIS SISWA SMP - Neneng Yunita; Tina Rosyana; Heris Hendriana (IKIP Siliwangi, 2018)
This study aims to determine the ability to think critically mathematically based on the motivation of junior high school students. The method in this research using correlational method with quantitative approach. The population in this study is in one of the junior high schools in western Bandung and the number of samples as many as 29 students with heterogeneous ability. Intrumen in this research is in the form of test of critical thinking ability capability with number of seven item and non test in the form of learning motivation scale which consist of 25 scale statement. The results of this study obtained that the ability to think critically mathematically based on learning motivation has a positive effect of 16.2%. While 83.8% influenced in addition to student learning motivation.